2014
DOI: 10.1371/journal.pone.0087226
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cx43 and NaV1.5 Expression Precede the Occurrence of Substantial Fibrosis in Calcineurin-Induced Murine Cardiac Hypertrophy

Abstract: In mice, the calcium-dependent phosphatase calcineurin A (CnA) induces a transcriptional pathway leading to pathological cardiac hypertrophy. Interestingly, induction of CnA has been frequently noticed in human hypertrophic and failing hearts. Independently, the arrhythmia vulnerability of such hearts has been regularly associated with remodeling of parameters determining electrical conduction (expression level of connexin43 (Cx43) and NaV1.5, connective tissue architecture), for which the precise molecular ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Moreover, we observed an increased expression of CTGF in control hearts after 16 weeks of pressure overload stimulation. This finding mirrors data from other studies that identified high CTGF expression levels under different cardiovascular pathological conditions as seen in patients and in experimental animal models, including applied pressure overload [8][9][10][11][12][13][14]. These studies, including our control hearts, show that CTGF is upregulated in the fibrotic heart suggesting the connotation of CTGF as a pro-fibrotic factor.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, we observed an increased expression of CTGF in control hearts after 16 weeks of pressure overload stimulation. This finding mirrors data from other studies that identified high CTGF expression levels under different cardiovascular pathological conditions as seen in patients and in experimental animal models, including applied pressure overload [8][9][10][11][12][13][14]. These studies, including our control hearts, show that CTGF is upregulated in the fibrotic heart suggesting the connotation of CTGF as a pro-fibrotic factor.…”
Section: Discussionsupporting
confidence: 90%
“…Increased levels of CTGF have been found in patients with heart failure, ischemia and coronary artery disease [8][9][10]. Similar elevations were observed in injury-induced animal models of cardiac hypertrophy and fibrosis [10][11][12][13][14]. The implication of CTGF in fibrosis development/maintenance, but also the close relationship with the pro-fibrotic cytokine transforming growth factor beta-1 (TGF-ÎČ1), is well documented [6,15].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Nava described the complete syndrome in 1987/1998 (1)(2)(3) and by a simple analysis of the ECG demonstrated that the ECG pattern was due to a right ventricular conduction disturbance linked to a structural abnormality of the right ventricle. These evidencebased theories received a lot of heavy criticism (and other unfair definitions and boycott), because experts have insisted the syndrome was idiopathic, linked to ion channel abnormalities in a totally normal heart.…”
Section: Search For Evidencebased Medicine For Brugada Syndromementioning
confidence: 99%
“…)-linked transcription factors. Indeed, work from our group and colleagues has associated common variation at the SCN5A-SCN10A locus with the risk for the Brugada syndrome compared with healthy controls(2,3). This locus is associated with a TBX3/5 binding site thought to regulate SCN5A transcription.It is therefore appealing to investigate how TBX3/5 may influence Connexin-43 expression and in turn influence the phenotype of the Brugada syndrome.Dr.…”
mentioning
confidence: 99%